Management of the bank's deposit policy in modern conditions - Zhang Zhenmin (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the deposit activity of banking institutions. The subject of research includes the theoretical, methodological, and practical foundations for improving the management of banks' deposit policies. The purpose of the master's thesis is to generalize the theoretical and methodological foundations for the formation and implementation of deposit policies in banks and to develop practical recommendations for improving deposit policy management in modern conditions. Based on the results of the research, theoretical and practical provisions have been formulated. The author has developed specific proposals for enhancing the management of deposit policies in banks, focusing on adaptability to modern challenges, including economic instability and martial law. The obtained results can be used to refine methodological approaches to deposit policy management in banking institutions. The findings are particularly valuable for JSC "UKRSIBBANK" and can be adapted by other banks seeking to enhance their competitiveness and financial stability in dynamic economic conditions.
Scientific advisor: Malafeiev T., PhD in public administration, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; banking institution; bank resources; deposits; deposit policy; deposit policy management